German-Turkish Relations Revisited: The European Dimension, Domestic and Foreign Politics and Transnational Dynamics - Turhan, Ebru (Nomos Verlagsgesellschaft mbH & Co. KG, 2019)
In recent years, dialogue between Germany and Turkey has increasingly become subject to political, academic and public debates. The evolution of the bilateral relations between both countries has been a journey with numerous ebbs and flows for a long time. Lately, however, phases of conflict have started to last longer and have included magnified levels of estrangement and mutual distrust. Is the complex and dynamic relationship between both countries heading from a ‘rollercoaster ride’ to a ‘train crash’? Departing from the intermestic and exceptionally interdependent nature of German-Turkish relations, this edited volume revisits the dialogue between Germany and Turkey and examines the potential for future cooperation and conflict between both countries. To this end, the chapters of this volume focus on three dimensions of German-Turkish relations which particularly involve conflictual and cooperative dialogue: the European dimension, domestic and foreign politics and transnational dynamics.With contributions by Mirja Schröder, Funda Tekin, Ebru Turhan, Thomas Krumm, Ludwig Schulz, Yaşar Aydın, Deniz Kuru, Defne Kadıoğlu Polat, Çetin Çelik, Elif Posos Devrani and Wolfgang Wessels